Use of Remdesivir in the treatment of Covid-19: na integrative review (Research, Society and Development, 2022)
The present study aimed to determine the efficacy, effectiveness and safety of Remdesivir in the treatment of Covid-19 through an integrative review. The search for articles was carried out in March 2021 in the Pubmed, Scielo, Embase and Cochrane databases. To guide this research, the guiding question was raised: “What is the role of Remdesivir in the treatment of Covid-19 in humans?”. The descriptors “Covid or Sars-Cov-2 or Coronavirus” and “treatment” and “Remdesivir” were used. Inclusion criteria were original primary studies that addressed the proposed topic, available in full, between 2019-2021, in Portuguese or English. Of the 3012 articles found, 17 were used that met the inclusion criteria. Most of the studies found reported an improvement in the condition of patients treated with Remdesivir, but it is important to note that therapy with the drug also had several side effects and did not change the mortality rate. Based on the data analyzed, Remdesivir showed promising results, suggesting a favorable risk-benefit profile, but as far as was observed, the rate of deaths was not altered and its prolonged use can trigger undesirable side effects.